Whitespotted eagle ray (Aetobatus narinari) age and growth in wild (in situ) versus aquarium-housed (ex situ) individuals: Implications for conservation and management - Boggio-Pasqua, Atlantine; Bassos-Hull, Kim; Aeberhard, William H.; Hoopes, Lisa A.; Swider, Denise A.; Wilkinson, Krystan A.; Dureuil, Manuel (Frontiers in Marine Science, 2022)
Elasmobranchs typically display slow growth, late maturity and low fecundity life history characteristics, making them vulnerable to fishing pressures and environmental perturbations. The whitespotted eagle ray (Aetobatus narinari), a large pelagic migratory ray with an endangered status on the IUCN Red List, fits this pattern based on available literature. Historically, age and growth parameters for this ray have been reported through vertebral ageing methods. However, the periodicity of vertebrate band pair formation, which is used for ageing, has not been validated for this species, making ageing accuracy and thus the resulting growth parameters uncertain. In this study, we used both a frequentist and Bayesian method of estimating sex-specific von Bertalanffy growth parameters (DW∞, k) in wild recaptured versus aquarium-housed rays. Additionally, we estimated growth from repeated measurement data collected from aquarium-housed rays, as an alternative approach to obtain growth parameters while allowing for individual variability. Between 2009 and 2020, 589 whitespotted eagle rays were caught, measured, tagged and released along the southwest coast of Florida. Of these rays, 34 were recaptured between 5–1413 days at liberty. Nineteen additional rays were collected during the same period, transported and maintained at Georgia Aquarium, Atlanta, where they were regularly weighted and measured. Data from Association of Zoos and Aquariums accredited facilities provided prior information on maximum size for the Bayesian estimations, and size at birth, size at maturity, and maximum life span. These data were used to plot and interpret von Bertalanffy growth curves. Wild whitespotted eagle rays were found to grow faster and mature earlier than previously thought, with Bayesian estimates of k = 0.28 year-1 in females, and k = 0.30 year-1 in males. Aquarium-housed individuals seemed to grow slower and reach smaller sizes, although data provided by the aquariums showed variable growth patterns depending on the facility. Longevity was estimated at 14-15 years in wild rays while maximum lifespan observed in aquariums was 19-20+ years. Life history parameters and growth trajectories generated from this study offer valuable information to aid with future conservation management strategies of this endangered species.